The Relevance of «Engañar para reinar» in the Dramatic Work of Antonio Enríquez Gómez (Castilla. Estudios de Literatura, 2021)
For several years, the figure of Antonio Enríquez Gómez has aroused the interest of the researchers who work in the Golden Theater in Spain and his works are being recovered and edited in order to deepen their knowledge of this author's dramatic work. This article aims to collaborate in the study of his theater by analyzing the most relevant points of a key comedy of his production, Engañar para reinar, probably the first of the comedies that Enríquez Gómez wrote.
Keywords: Antonio Enríquez Gómez; Spanish Golden Age theatre; text editing; authorship